2015
DOI: 10.4172/2155-6148.1000557
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Spinal Anesthesia Induced Hypotension in Elderly: Comparison of Prophylactic Atropine with Ephedrine

Abstract: Background: Spinal anesthesia induced hypotension is more common and hazardous in elderly, as they have decreased physiological reserve and compromised blood supply to various vital organs. Reversal of the blunted reflexes of tachycardia following hypotension in elderly with atropine or ephedrine may help in prevention of hypotension.Methodology: Present study is a prospective, randomized, double blind, controlled trial where sixty ASAPS I-II patients undergoing urological surgeries were assigned to receive ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(19 reference statements)
3
0
0
Order By: Relevance
“…Another RCT that compares atropine and ephedrine with a placebo showed MAP was comparable between atropine and ephedrine groups but in placebo group MAP was signi cantly low compared to other groups [19]. This is also in line with our ndings showing a better maintenance of MAP after spinal anesthesia in the atropine exposed group than un-exposed group especially in the rst 30 minutes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another RCT that compares atropine and ephedrine with a placebo showed MAP was comparable between atropine and ephedrine groups but in placebo group MAP was signi cantly low compared to other groups [19]. This is also in line with our ndings showing a better maintenance of MAP after spinal anesthesia in the atropine exposed group than un-exposed group especially in the rst 30 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study the occurrence of tachycardia had no signi cant difference between exposed and unexposed groups. This was also in line with other studies that showed the re ex tachycardia after atropine prophylaxis in patients undergoing urological procedures under spinal anesthesia is not statistically signi cant [2,6,19].…”
supporting
confidence: 92%
See 1 more Smart Citation